ANALISA RISK ASSESMENT BERDASARKAN PERMENKES NO. 25 TAHUN 2019 DI UNIT LABORATORIUM, LPFK KEMENKES X - Ani, Nur; Wartini, Wartini; Julia, Pertiwi; Titik, Haryanti; Iik, Sartika (Universitas Veteran Bangun Nusantara, 2024)
Urgency: Working in a laboratory often brings us into contact with hazardous chemicals, flammable materials, sharp objects, blood, hazardous specimens, and various heavy equipment. Based on a preliminary study on December 8, 2023, the LPFK Kemenkes Banjarbaru is an agency that has collaborated with FKMIK in terms of the Tri Dharma of Higher Education. The results of a preliminary study conducted on December 8, 2023 at the LPFK Kemenskes Banjarbaru, it is known that in the work process there are potential risks whose risk profiles and risk categories are not yet known. Where these risks will interfere with organizational processes and must be controlled. Objective: This study aims to identify hazards, determine the level of danger, group risk profiles and risk categories. The importance of this research is to reduce the risk of work accidents, making it one of the references for reducing the number of work accidents. Method: This type of research is descriptive qualitative, the research variables used are single variables, namely risk assessment/risk management, the targeted outputs in this study are indexed publications in Sinta 3 and pocket books. Result : The results of risk identification in the laboratory work unit at LPFK X based on the assessment of the standard of Permenkes No. 25 of 2029 have the potential for Quality risk hazards and K3 risk hazards as stated in the risk code LPDP.01.01 to LPDP.01.12. The results of the risk assessment analysis have the potential for low risk hazards for 3 activities, medium risk for 8 activities and high risk for 1 activity. The results of the risk category based on the standard assessment have the risk categories of Legal Risk, Reputation Risk, Operational Risk, Financial Risk, and Compliance Risk.